Comparison of Three Total Ankle Replacement Systems Done at a Single Facility. Issue 1 (February 2017) - Coetzee, J. Chris; Petersen, Daryle; Stone, Rebecca M.
Background. Ankle replacement surgery is an established and accepted way to treat end stage ankle arthritis. Though there are multiple publications looking at results with various ankle replacement systems, most of them are single implant longitudinal studies from a single institution. There are, however, no prospective randomized studies evaluating the outcomes of different total ankle arthroplasty (TAA) systems; in fact, there are no comparative studies at all. Methods. The comparative results of 3 different total ankle systems (INBONE, STAR, and Salto Talaris) were evaluated. All the TAA system implants were performed at a single institution from 2007 to 2011. The data were evaluated by authors completely independent from the study institution. The goal was to look at the results in an objective, noninstitution perspective. Results. At minimum 2-year follow-up there is no statistical difference in outcomes scores or functional tests between the INBONE, STAR, or Salto Talaris, with all 3 TAA systems resulting in statistically significant improvement of all parameters since baseline. Conclusions. This is the first study that compares the results of 3 different total ankle replacement systems done at a single institution over the same period of time. Even though it is not a randomized study, it gives a valuable perspective of the short-term results. Levels of Evidence: Therapeutic, Level IV: Case series